Suerte maldita - Miller, Danny (Crime fiction writer); Jiménez Arribas, Carlos, 1966-; Miller, Danny (Crime fiction writer). ([Madrid] : Siruela, 2016)
London 1965, and Vince Treadwell investigates the seemingly unrelated murders of a playboy aristocrat from Belgravia and a young black nurse from the wrong side of town. It takes the detective to the illegal drinking dens of Notting Hill run by the self-styled Black Power leader, Michael X; the nightclubs of Soho owned by the legendary gangster, Billy Hill; and the exclusive gaming tables of the Montcler Club in Berkeley Square, where the blue bloods and power players of England gamble thousands on the turn of a card. But as Vince Treadwell digs deeper he finds himself not only embroiled w.
Online resource; title from ePub title page (Digitalia, viewed April 21, 2017)
Keywords: Murder -- Investigation -- Fiction; Aristocracy (Social class) -- Fiction; Thrillers (Fiction); Spy fiction; Noir fiction; Electronic books